The Influence of Firm Size, Leverage, and Profitability on Firm Value - Thahir, Yuri Arlin; Sofhian (Gorontalo Accounting Journal, 2026)
This study examined the effect of firm size, proxied by the natural logarithm of total assets, leverage, proxied by the debt-to-equity ratio (DER), and profitability, proxied by return on assets (ROA), on firm value, proxied by the price-to-book value (PBV), both simultaneously and partially. The sampling technique employed was purposive sampling, resulting in a sample of 15 companies that met the selection criteria. Panel data regression analysis was conducted using EViews version 13 software. The results indicated that firm size had a significant partial effect on firm value, whereas leverage and profitability did not have significant effects. However, simultaneously, firm size, leverage, and profitability had a significant effect on firm value.